1981
DOI: 10.1002/1520-6807(198101)18:1<28::aid-pits2310180107>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of learning disabled college students' achievement from WRAT and PIAT grade, standard, and subtest scores

Abstract: Although there have been a number of studies that compared the test results of the Wide Range Achievement Test (WRAT) and the Peabody Individual Achievement Test (PIAT), none had been accomplished with a group of college-aged learning disabled students. Indeed, few researchers had investigated populations over 16 years of age, and none had compared grade scores and standard scores with appropriate subtest scores as derived from these two instruments. With the recent emphasis on postsecondary education for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Silverstein (1978) undertook a direct investigation of the standardization of the WRAT, and with an American sample found that the 1976 WRAT norms tended to overestimate actual achievement level. Cordoni & Snyder (1981) suggested that the WRAT overestimated achievement, especially in arithmetic, for their sample of over-16-year-olds. Pikulski and Shanahan (1982) diagnostically evaluated disabled readers with ages ranging from 7 years 2 months to 15 years 11 months.…”
mentioning
confidence: 99%
“…Silverstein (1978) undertook a direct investigation of the standardization of the WRAT, and with an American sample found that the 1976 WRAT norms tended to overestimate actual achievement level. Cordoni & Snyder (1981) suggested that the WRAT overestimated achievement, especially in arithmetic, for their sample of over-16-year-olds. Pikulski and Shanahan (1982) diagnostically evaluated disabled readers with ages ranging from 7 years 2 months to 15 years 11 months.…”
mentioning
confidence: 99%